The effect of miR‐340 over‐expression on cell‐cycle–related genes in triple‐negative breast cancer cells. (27th May 2016) - Mohammadi Yeganeh, S.; Vasei, M.; Tavakoli, R.; Kia, V.; Paryan, M.
Abstract : Breast cancer is a heterogeneous disease, and among all types, triple‐negative breast cancer (TNBC) is characterised by high risk of recurrence. The discovery of microRNAs (miRNA) has opened the door for targeted therapy of TNBC. miR‐340 down‐regulation and sub‐G1‐accumulated cells in flowcytometry were observed in metastatic TNBC cells (data in publication), leading us to investigate the potential tumour suppressive role of this miRNA on cell‐cycle–related genes. A lentiviral vector containing miR‐340 was applied to over‐express miR‐340 in TNBC cell line, MDA‐MB‐231. Then, the expression of some cell‐cycle–regulating genes including cyclin A2 ( cyclin A2 ), Cyclin‐dependent kinases 2 ( CDK2 ), cyclin‐dependent kinase inhibitors ( P16, P18 and P27 ), Retinoblastoma ( RB ) and transcription factors ( SMAD 4, SOX2 and SOX17 ) was investigated using quantitative RT‐PCR. The results showed a decline in the expression of SOX2, P16 and P27 after miR‐340 over‐expression, whereas we observed an increase in the expression of cyclin A2, CDK2, SOX17, P18, SMAD 4 and RB . The over‐expression of tumour suppressor genes such as RB and SOX17 and down‐regulation of an oncogene such as SOX2 were in accordance to the inhibitory role of miR‐340 that causes blockage of breast cancer metastasis which should be further investigated.